Thinking of Water in the Early Second Temple Period - Ben Zvi, Ehud,Levin, Christoph (De Gruyter, 2014)
Water is a vital resource and is widely acknowledged as such. Thus it often serves as an ideological and linguistic symbol that stands for and evokes concepts central within a community. This volume explores 'thinking of water' and concepts expressed through references to water within the symbolic system of the late Persian/early Hellenistic period and as it does so it sheds light on the social mindscape of the early Second Temple community.
Description based on publisher supplied metadata and other sources
Keywords: Konferenzschrift; Wasser; Frühjudentum; Literatur; Water – Paletine – Social aspects; Water – Religious aspects – Judaism; Water in rabbinical literature